ANALISIS NARATOLOGI GÉRARD GENETTE DALAM FILM SORE : ISTRI DARI MASA DEPAN - Meilanie Sartika, Mauliddya; Fahmy Dalimunthe, Syairal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the narratological structure of Yandy Laurens' film "Sore: Istri dari Masa Depan" (The Wife of the Future), using Gerard Genette's narratological theory. This research is motivated by the complexity of the film's timeline, which features temporal deviations and diverse narrative perspectives, particularly through the character Sore's experience of repeating time to change Jonathan's fate in the future. The issues examined include the forms of time deviation (Narrative Time) and temporal data, namely: (Order), (Analepsis and Prolepsis), (Duration), (Frequency) of repeated events, and (Focalization of Mood) and the film's point of view. The method used in this study is descriptive qualitative. Data were obtained through observation and note-taking techniques of scenes and dialogue in the film "Sore: Istri dari Masa Depan." Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that the Narrative Time analysis (temporary data) in the film consisted of 36 data points divided into three main categories. The 20 data items, "Order" (time sequence), demonstrate the dominant use of analepsis (flashback), prolepsis (flashforward), and a combination of both in constructing the storyline. The "Duration" (time duration) (13 data items) illustrates variations in the presentation of time through scenes, summaries, ellipsis, and pauses. The "Frequency" (repeated events) (3 data items) indicates the repetition of events through singulative, repetitive, and iterative forms. Meanwhile, the "Focalization of Mood" (point of view) (6 data items) demonstrates the narrative perspective through zero, internal, and external focalization. Primary data from the film were analyzed through a literature review and Genette's narrative approach, with theoretical benefits enriching narratological studies. It can be concluded that the narrative structure in this film is constructed through complex narrative time deviations and points of view, which not only reinforce the story's conflict but also emphasize the character Sore's efforts to change the future through the choices he makes.